Pengaruh Socıal Perceptıon, Socıal Cultural Envıronment, Entrepreneur Orıentatıon Terhadap Mınat Berwırausaha Mahasıswa Dı Indonesıa [The Influence of Socıal Perceptıon, Socıal Cultural Envıronment, Entrepreneur Orıentatıon on Entrepreneurial Interest of Students in Indonesia] - Chin, Vicky; Innocentius Bernarto (Indonesian Marketing Journal, 2024)
This study aims to determine the effect of social perception, socio-cultural environment, entrepreneurial orientation on female students' entrepreneurial interest in Indonesia. This study uses a quantitative method with data collection methods, namely by using an online questionnaire created via Google Form and distributed to online messengers (LINE, WhatsApp, and Telegram). The technique used to determine the sample in this study was using consecutive sampling with a total of 250 respondents. The results of the hypothesis test show that all hypotheses are supported, namely that there is a positive influence from the Socio-Cultural Environment which has a positive effect on Female Student Entrepreneurship Orientation, Social Perception has a positive effect on Female Student Entrepreneurship Orientation, Entrepreneurship Orientation has a positive effect on Female Student Entrepreneurial Intentions, Socio-Cultural Environment has an effect positive effect on Female Student Entrepreneurial Intentions, Social Perception has a positive effect on Female Student Entrepreneurial Intentions, Entrepreneurial Orientation mediates the influence of Socio-Cultural Environment on Female Student Entrepreneurial Intentions, Entrepreneurial Orientation mediates the influence of Social Perception on Female Student Entrepreneurial Intentions. Abstrak Bahasa Indonesia: Penelitian ini bertujuan untuk mengetahui pengaruh dari Pengaruh Social Perception, Social Cultural Environment, Entreprenuer Orientation Terhadap Minat Berwirausaha Mahasiswi di Indonesia. Penelitian ini menggunakan metode kuantitatif dengan metode pengumpulan data yaitu dengan menggunakan kuisioner online yang dibuat melalui google form dan disebarkan ke online     messenger (LINE, WhatsApp, dan Telegram). Teknik yang digunakan untuk menentukan sampel dalam penelitian ini adalah menggunakan consecutive sampling dengan jumlah responden sebanyak 250 responden. Hasil uji hipotesis menunjukkan hasil bahwa seluruh hipotesis didukung, yaitu terdapat pengaruh positif dari socio-cultural environment berpengaruh positif terhadap entrepreneurial orientation Mahasiswi Wanita, social perception berpengaruh positif terhadap entrepreneurial orientation Mahasiswi Wanita, entrepreneruial orientation berpengaruh positif terhadap entrepreneurial ıntention Mahasiswi Wanita, socio-cultural environment berpengaruh positif terhadap entrepreneurial ıntention Mahasiswi Wanita, social perception berpengaruh positif terhadap entrepreneurial ıntention Mahasiswi Wanita, entrepreneurial orientation memediasi pengaruh social-culture environment terhadap entrepreneurial ıntention Mahasiswi Wanita, entrepreneurial orientation memediasi pengaruh social perception terhadap entrepreneurial ıntention Mahasiswi Wanita.